Mises and Hayek Dehomogenized - Salerno, Joseph T. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
Since its revival in the early 1970s, what was called “Austrian economics” has been regarded by most of its contemporary adherents as the outgrowth of a unified tradition that can be traced back to Carl Menger. This paper challenges this view and argues that in fact two very different traditions grew out of Menger’s work. One tradition can be traced back to the works of F. A. Hayek to Friedrich Wieser, one of Menger’s most prominent followers. The other tradition stems from the writings of Menger’s other leading disciple, Eugen von Böhm-Bawerk, and includes the latter’s student Ludwig von Mises. This essay defends the thesis that these two separate traditions exist and have been confused with modern Austrians.